Electro-characteristics of Myocardial Pouches and Reduction of the Frequency of Steam Pops During Radiofrequency Ablation - Luo, Jianfeng; Guo, Fei; Zhu, Hongjun; Su, Hao; Wu, Yuanbo; Zhu, Jing; Zhang, Can; Xu, Jian (Frontiers in Physiology, 2022)
Background: Radiofrequency ablation (RFA) effectively treats atrial fibrillation. Steam pop (SP) is a dangerous complication of RFA, which can lead to pericardial tamponade or even death. Objective: This study aimed to explore the Electro-characteristics of myocardial pouches, and the relationship between SP, pouch, and impedance. Methods: Swine myocardium was divided into the pouch group and smooth myocardium group. Continuous RFA at 50 W was applied. The initial impedance reduction within the first 3 s of ablation, and the time from the start of ablation to SP were recorded. After enabling the delta impedance cutoff function, RFA was performed at different percentage of delta impedance (PDI) cutoff thresholds. Results: The impedance was higher for the pouch myocardium compared to the smooth myocardium (123.22 ± 8.63 Ω and 95.75 ± 4.75 Ω, respectively; p < 0.001). The RFA duration before SPs was shorter in the pouch group compared to the smooth myocardium group (9 s [interquartile range, IQR: 6.25–13 s] and 33 s [IQR: 26.25–40.75 s], respectively; p < 0.001]. Within the first 3 s of RFA, impedance reduction (24.65 ± 6.57 Ω and 12.78 ± 3.35 Ω, respectively; p < 0.001) and PDI (19.18% [IQR: 16.39–24.20%] and 12.96% [IQR: 11.17–14.39%], respectively; p < 0.001) were greater in the pouch group compared to the smooth myocardium group. A PDI of 15% and delta time of 3 s effectively reduced the frequency of SPs without seriously affecting RFA use. Conclusions: SPs occur more frequently in the pouch area during RFA. Appropriate delta impedance cutoff settings (PDI: 15%; delta time: 3 s) can reduce the frequency of SPs and improve the RFA safety.